2017
DOI: 10.1021/acs.jafc.7b01920
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Synthetically Administered and Endogenous Thiouracil Based on Monitoring of Urine, Muscle, and Thyroid Tissue: An in Vivo Study in Young and Adult Bovines

Abstract: Thiouracil (TU), synthesized for its thyroid-regulating capacities and alternatively misused in livestock for its weight-gaining effects, is acknowledged to have an endogenous origin. Discrimination between low-level abuse and endogenous occurrence is challenging and unexplored in an experimental setting. Therefore, cows (n = 16) and calves (n = 18) were subjected to a rapeseed-supplemented diet or treated with synthetic TU. Significant higher urinary TU levels were recorded after TU administration ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…The origin of these "background" levels in the control animals is unknown. However, this was also observed in a thiouracil treatment study for calves and cows performed by Wauters (Wauters et al 2017). This study hypothesised that thiouracil's origin in the control group could be from other feed ingredients from plants, which possibly also contained glucosinolate-like or chemicalrelated compounds, which could form thiouracil.…”
Section: Control Groupsupporting
confidence: 53%
See 2 more Smart Citations
“…The origin of these "background" levels in the control animals is unknown. However, this was also observed in a thiouracil treatment study for calves and cows performed by Wauters (Wauters et al 2017). This study hypothesised that thiouracil's origin in the control group could be from other feed ingredients from plants, which possibly also contained glucosinolate-like or chemicalrelated compounds, which could form thiouracil.…”
Section: Control Groupsupporting
confidence: 53%
“…After treatment, in the first week, concentrations were between 35 and 4600 µg/L and during the second week between 0.8 and 47 µg/L. In the study of Wauters (Wauters et al 2017), the first week after treatment showed a swift decline of thiouracil in bovines, even below 10 µg/L. This difference could be due to the metabolism of porcine, which is different from cows.…”
Section: Thiouracil 02 and 2 G/100 Kg Treated Groupmentioning
confidence: 95%
See 1 more Smart Citation
“…Urine samples that were considered for metabolic fingerprinting have previously (after about a half year of storage) also been analyzed in a targeted fashion using a triple quadrupole instrument, whereby TU concentrations were determined using matrix-matching calibration curves [ 16 ]. TU concentrations, as discussed in this manuscript, were thus obtained by the cited targeted approach.…”
Section: Methodsmentioning
confidence: 99%
“…TU in urine and thyroid tissue [ 13 ]. Unfortunately, a systematic occurrence of urine samples, exceeding this recommended TU concentration, has been observed in recent years [ 14 , 15 , 16 ]. Therefore, national and international surveys have been conducted to set a new threshold value that is more accurate to differentiate between exogenous and semi-endogenous TU [ 5 ].…”
Section: Introductionmentioning
confidence: 99%